Obtenção e caracterização de nitreto de boro hexagonal - Gonçalves, Augusto Nobre (2016)
This work proposes alternative obtainment and characterization of two bidimensional nanomaterial: graphene and hexagonal boron nitride (h-BN). The graphene synthesis considers two variables, the under pressure diffusion of graphite powder in phyllosilicate powder and the exfoliation of homogenized pressed body by sonication in presence of a dispersant. This research aims to contribute prposing alternative techniques for the graphene production research that can result in a robust process with generation of large masses of the material. Through the proposed technique it was possible to contemplate significant volume of few layers graphene. However, the low particle size of the original graphite used only generated graphene with micrometric dimensions. The h-BN presented synthesis aimed to resolve two industrial problems associated with h-BN synthesis: the high temperature required for material calcination and the exclusion of sodium azide as a process reactant. The sodium azide is toxic and has high commercialization value and its purchase is controlled by military. The results indicate that proposed synthesis is effective in reducing the calcination temperature of the h-BN to below 1000 °C without the use of sodium azide. However, there are environmental control requirements to perform the technique as a result of the large volume of ammonia released by the system.